Efficacy and safety of inetetamab-containing regimens in patients with HER2-positive metastatic breast cancer in first-line/second-line setting - Zhang, Jian; Mu, Yuxin; Zhang, Hui; Deng, Chao; Yang, Jiao; Gan, Lu; Yang, Qingmo; Xu, Xuefeng; Liang, Wanping; Qi, Xiaowei; Xu, Liang (Frontiers in Oncology, 2025)
BackgroundInetetamab is a novel recombinant humanized anti-Human epidermal growth factor receptor 2 (HER2) monoclonal antibody. This real-world retrospective study assessed the efficacy and safety of inetetamab-containing regimens in first-line/second-line treatment of HER2-positive metastatic breast cancer (MBC).MethodsThis study retrospectively recruited HER2-positive MBC patients who received inetetamab- containing regimens from June 2020 to May 2023. The outcomes included progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR).ResultsA total of 329 patients were enrolled and included in the efficacy analysis. The most frequently used treatment strategy was contained inetetamab plus pyrotinib (205/329, 62.3%). Patients treated with first-line regimens benefited the most, with a median PFS of 15.0 versus (vs.) 10.0 months (first-line- vs. second-line inetetamab plus pyrotinib, p <0.001), 19.0 vs. 17.0 months (first-line- vs. second-line inetetamab plus pertuzumab, p=0.096), and 13.0 vs. not reached months (first-line- vs. second-line inetetamab plus chemotherapy, p=0.229). The complete response (CR) was observed in 16 (4.9%) patients of all cohort, with the ORR was 51.1% (95% confidence interval [CI], 45.7%-56.4%), and the DCR was 96.4% (95% CI, 93.7%-97.9%). The grade 3 or higher adverse events (AEs) were observed in 29.5% of the whole study cohort. Diarrhea (39.2%), white blood cell count decreased (33.0%), and myelosuppression (18.6%) as the most frequent ones.ConclusionsFollowing the first- and second-line of treatment, inetetamab- containing combinations demonstrated promising clinical activity and a manageable safety profile in patients with HER2-positive MBC, especially in the first-line treatment.